2016
DOI: 10.1007/s13592-016-0438-6
|View full text |Cite
|
Sign up to set email alerts
|

Male remating and its influences on queen colony foundation success in the bumblebee, Bombus terrestris

Abstract: -In most bumblebee species, queens mate with only one male, but males can mate more than once. However, the effects of male remating on colony foundation success of queens remain poorly understood. To test for effects of male remating, we assigned Bombus terrestris queens randomly to one of two groups: virgin males or nonvirgin males that have mated once before. When males were allowed to mate for a second time with virgin queens, 58.57 % successfully remated. There was no significant difference in queen hiber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 32 publications
(43 reference statements)
2
12
0
Order By: Relevance
“…However, the above-mentioned behavior of male patrolling cannot be observed in small experimental flight cages (Djegham et al 1994;Sauter and Brown 2001). Previous studies showed that mating success in confinement can be influenced by several factors, such as temperature, photoperiod, adult age and size, male dimension, and experience (Tasei et al 1998;Kwon et al 2006;Amin et al 2007;Amin et al 2010;Amin et al 2012;Gosterit and Gurel 2016). Evidence indicates that wild populations of B .…”
Section: Introductionmentioning
confidence: 99%
“…However, the above-mentioned behavior of male patrolling cannot be observed in small experimental flight cages (Djegham et al 1994;Sauter and Brown 2001). Previous studies showed that mating success in confinement can be influenced by several factors, such as temperature, photoperiod, adult age and size, male dimension, and experience (Tasei et al 1998;Kwon et al 2006;Amin et al 2007;Amin et al 2010;Amin et al 2012;Gosterit and Gurel 2016). Evidence indicates that wild populations of B .…”
Section: Introductionmentioning
confidence: 99%
“…We have described a new agent-based systems model, Bumble-BEEHAVE, rich in structural realism and mechanism that can be used to examine the effects of multiple stressors on bumblebee colonies and populations over multiple years, in realistic landscapes. It TA B L E 3 Results of simulations in a realistic landscape compared to empirical data from literature (Duchateau & Velthuis, 1988;Gosterit & Gurel, 2016). Mean (±SD) of each output per colony or replicate is given.…”
Section: Discussionmentioning
confidence: 99%
“…N replicates = number of replicates and compared to Knight et al (2005) Note. a Calculated from table II in Gosterit and Gurel (2016). b 6.42 days before eusocial phase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations